Compósitos funcionais de polímeros condutores com magnetita: Síntese, caracterização e aplicação - Zanotto, Caroline (2021)
This study presents the production of composites formed between Polyaniline and Magnetite (Pani-Mag) aiming at an easy, simple and more economical synthetic route, analyzing parameters that satisfactorily contemplate the principles of green chemistry to show how environmentally sustainable and economically interesting this new material can to be. The production of new materials for technological application also needs to be focused on less waste generation and greater sustainability. Thinking about cleaner chemical procedures, with low waste generation, less consumption of raw materials and energy, has represented a critical challenge to the development of technologically sophisticated devices for the development of electrochemical sensors or electronic capacitors. With these assumptions in mind, adaptations were made in the routes described in the literature for the synthesis of materials, producing 3 different composite materials designated as Pani-Mag 01 and Pani-Mag 02. Previous studies and preliminary results selected 2 samples of magnetite to continue the second stage of synthesis, which was the formation of the composite with Pani. For the third material, Pani-Mag 1E, a one-step synthesis was sought by precipitating magnetite directly into the Pani chains. As a result for Pani-Mag 01, in which the synthesis was performed with less vigorous agitation, through a mechanical stirrer built by the doctoral student with alternative materials, formation of material characteristic to the composite in question was observed. This was confirmed by the analysis of FTIR, DRX, MEV spectra. From the results of the analysis of the Pani-Mag 02 composite, the FTIR and DRX spectra confirm that more intense interactions occurred between the polymeric phases and the oxide particles, enhancing applications. Saturation magnetization resulted in a value of 33.5 emu g-1, which is compatible with reference values in the literature for Pani-Mag composites. Electrochemical tests indicate an electrochemically stable material with the potential to be applied as an electrochemical sensor in the determination of ascorbic acid in solution. Regarding the Pani-Mag 01 composite, it showed more satisfactory results. For the analysis of the metric of the green chemistry, both composites presented IPE of 65%, being satisfactory for some pre-established criteria. The Pani-Mag 1E composite showed spectroscopic, structural and morphological characteristics of a characteristic Pani-Fe3O4 composite, well evidenced by X-ray diffractometry and magnetic measurement data. The magnetization value in the non-saturating field B = 20 kOe was 1.57 emu g-1 which is potentially suitable for applications in electrochemical devices, adsorption of contaminants or capacitors. The construction of the metric tables of synthesis, according to the Green Star criteria, to classify all chemical substances, regarding their risks to the environment, human health and physicists, resulted in an IPE star fill index of 60%, which meets safety principles and indicates which aspects are still open to further improve the synthetic route. These composites proved to be promising for several applications such as sensors for molecules of interest, capacitors, among others, being satisfactory for the purposes of this study.